2018
DOI: 10.1002/etc.4045
|View full text |Cite
|
Sign up to set email alerts
|

Sewage sludge biochars management—Ecotoxicity, mobility of heavy metals, and soil microbial biomass

Abstract: Production of biochar from sewage sludge may be a promising solution for sewage sludge management and improvement of soil properties, including carbon dioxide sequestration. The aim of the present study was to compare the effects of biochars derived from different sewage sludges on soil physicochemical and biological properties, ecotoxicity, and plant yield. Three biochars (produced at a temperature of 300 °C) were applied into sandy acid soil in doses of 0.5, 1, and 2% (w/w). Depending on the type and dose, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(18 citation statements)
references
References 43 publications
5
12
0
1
Order By: Relevance
“…The increase in pH was significantly lower than that reported by Jin et al [39], but it has to be pointed out that in the case of Jin et al's research, the process temperature was much higher (400 and 600 • C). The increase in pH value in the present experiment was similar to the result shown by Mierzwa-Hersztek et al [35]. The neutral pH range is desirable, as the mobility of HMs tends to be low [40].…”
Section: Heavy Metal Leachability From Biochars In Relation To Torrefsupporting
confidence: 92%
“…The increase in pH was significantly lower than that reported by Jin et al [39], but it has to be pointed out that in the case of Jin et al's research, the process temperature was much higher (400 and 600 • C). The increase in pH value in the present experiment was similar to the result shown by Mierzwa-Hersztek et al [35]. The neutral pH range is desirable, as the mobility of HMs tends to be low [40].…”
Section: Heavy Metal Leachability From Biochars In Relation To Torrefsupporting
confidence: 92%
“…For example, poultry litter feedstocks are normally rich in S, Na, and Cl and so are the chars obtained from them ( Cantrell et al, 2012 ; Novak et al, 2013 ). In the case of sewage sludge, there is a wide variation in element content; however, S and Na are abundant and concentrated in derived biochars, as has been reported in other studies ( Lu et al, 2012 ; Song et al, 2014 ; Mierzwa-Hersztek et al, 2017 ).…”
Section: Discussionsupporting
confidence: 63%
“…In the study, Oleszczuk et al [63] reported slightly different relationships-the tested biochars were more toxic to V. fischeri than to L. sativum. Other studies by Mierzwa-Hersztek et al [64] showed that the type of feedstock from which biochars were produced has a significant effect on the toxicity of biochars. According to Ribeiro et al [59], ash amendment and ash + sludge amendment resulted in similar Lolium perenne growth compared to the control.…”
Section: Phytotoxicity Of Biomass Ashmentioning
confidence: 99%